PENERAPAN KARAKTER PROFETIK DI SD MUHAMMADIYAH 1 PANJI KABUPATEN SITUBONDO TAHUN 2017-2018 - Reky Lidyawati (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2018)
Character problems in people's lives continue to experience increasingly complex developments, scientific and technological progress has reformed the probability of character not only in the real world but also in cyberspace. This moral problem must be overcome to realize a society with moral character. In order to realize a society with good character, a process is needed to shape Islamic character, if we refer to Islamic character, then we will find the figure of our good character, the Prophet. As we have understood together that the Prophet is ma'sum and the akhlaq is al qur'an, it is proper for the Prophet or Prophet Muhammad to be a model in shaping each person's personal character. The process of forming this Islamic character must be implemented in formal education, especially in elementary level formal education, because children in primary school age are very easy to be directed and formed their personality so as to manifest an Islamic character or personality. This study aims to determine the application of prophetic characters in Muhammadiyah 1 Panji Elementary School by using descriptive qualitative research methods that seek to uncover the facts of research, research that describes an object with regard to the case research problem, because the author aims to intensively study one's background. , group or institution, in detail and in depth to the organization of a particular institution or symptom. From the discussion about the application of the prophetic character above, it can be concluded that the application of the prophetic character at Muhammadiyah 1 Panji Elementary School is carried out with; Intensive Supervision, Providing Strengthening Learning, Providing more intensive Islamic education, Providing longer learning hours, Evaluating Learning and School Data Collection